The Effects of Antioxidants on the Changes in Volatile Compounds in Heated Welsh Onions (Allium fistulosum L.) during Storage - Sang Mi Lee; Dami Kim; Young-Suk Kim (Molecules, 2022)
Welsh onion (Allium fistulosum L.) is usually used to enhance the flavor characteristics of various foods. Volatile compounds in Welsh onions, including sulfur-containing compounds, may vary during heat process and storage. Accordingly, the changes in the volatile compounds in Welsh onions, subjected to heat and antioxidant (ascorbic acid and glutathione) treatments during storage, are investigated in the present study. The majority of sulfur-containing compounds in Welsh onions showed significant differences between the untreated Welsh onions and heated Welsh onions. During the heating of the Welsh onions, some sulfur-containing compounds, such as 2-methylthiirane, 1-(methyldisulfanyl)prop-1-ene, 1-[[(E)-prop-1-enyl]disulfanyl]propane, 1-(propyltrisulfanyl)propane, 1-[[(E)-prop-1-enyl]trisulfanyl]propane, and (methyltetrasulfanyl)methane, showed significant differences between the untreated and heated Welsh onions (p < 0.05). In addition, partial least square discriminant analysis (PLS-DA) was applied to discriminate the heated Welsh onion samples added with different antioxidants. The heated Welsh onion samples added with ascorbic acid was mainly associated with 2-phenylacetaldehyde, acetic acid, methylsulfanylmethane, prop-2-ene-1-thiol, undecan-2-one, and (2E,4E)-deca-2,4-dienal. Moreover, the key volatile compounds in the heated Welsh onion samples added with glutathione were 3-ethylthiophene, 1-(methyldisulfanyl)-1-methylsulfanylpropane, 1-methylsulfanylpentane, 2-prop-2-enylsulfanylpropane, and 1-propan-2-ylsulfanylbutane.